Effect of high-intensity exercise on Gamma-Glutamyl Transferase levels in novice athletes. - Khan, Alamgir; Muhammad Zafar Iqbal Butt; Saleem Akhtar; Sanam Shehzadi; Manzoor Khan; Hozaifa Bin Asif; Aqib Ashraf (International Journal of Endorsing Health Science Research, 2025)
Background: The liver plays a critical role in various physiological functions, including metabolism, detoxification, and immune response. Gamma-glutamyl transferase (GGT) is an essential enzyme involved in glutathione metabolism and serves as a biomarker of oxidative stress and liver function. This study aimed to examine the effect of high-intensity exercise on GGT levels among novice athletes. Methodology: An experimental research study was conducted among male athletes registered at the Gymnasium of the University of the Punjab, Lahore, Pakistan. Twenty (20) participants were voluntarily selected and randomly assigned to two groups: the Control Group (CG) and the Experimental Group (EG), with ten (10) subjects in each. The EG followed an eight-week high-intensity exercise protocol, while the CG maintained their usual physical activity routine. Blood samples (5 ml) were collected from all participants and labeled with unique identification codes. GGT tests were performed to assess potential risks and benefits associated with high-intensity exercise. Results: The study findings revealed a significant impact of high-intensity exercise on GGT levels. In the EG, the pre-test mean GGT levels were 16.65±0.88, which increased to 24.15±1.39 post-intervention. Similarly, in the CG, the pre-test levels were 15.61±0.84, rising to 23.20±1.32. The observed differences were statistically significant (p < 0.05), indicating that high-intensity exercise influences GGT concentrations in novice athletes. Conclusion: It is concluded that the high-intensity exercise significantly impacts GGT levels, potentially due to increased metabolic activity and oxidative stress adaptation.